2023
DOI: 10.1177/01455613231176170
|View full text |Cite
|
Sign up to set email alerts
|

Full Endoscopic Resection of Intralabyrinthine Schwannomas: A Case Series

Abstract: Objective: To investigate the technique and efficacy of fully endoscope resection of intralabyrinthine schwannomas (ILS) by transcanal transpromontorial endoscopic approach (TTEA). Study Design: Retrospective case review. Setting: Hospital. Patients: All patients who were affected by ILS, without extension to the internal auditory canal and underwent surgery with TTEA in our hospital in 2020. Intervention(s): Therapeutic. Main Outcome Measure(s): Recovery status, postoperative complications and remaining sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…but complaints of transient episodes of vertigo (1-3 s) when climbing or lifting heavy objects." [35]. Endoscopic approaches for the surgical removal of intracochlear schwannomas with or without extension to the fundus of the IAC have also been suggested by other authors [36,37].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…but complaints of transient episodes of vertigo (1-3 s) when climbing or lifting heavy objects." [35]. Endoscopic approaches for the surgical removal of intracochlear schwannomas with or without extension to the fundus of the IAC have also been suggested by other authors [36,37].…”
Section: Discussionmentioning
confidence: 91%
“…Laborai et al (2022) showed that vestibular disfunction (areflexia to caloric test and reduced ipsilateral vHIT gain) of a patient with an intracochlear schwannoma treated with a “CI through tumour” strategy remained unchanged after the surgery “with just a slight increase in VOR asymmetry in the vHIT from 41% to 57% at one month and to 64% at six months” [ 34 ]. Wu et al (2023) reported a case of endoscopic surgical removal of an intracochlear IES with “no severe episodes of vertigo at follow-up for 11 months to 2 years … but complaints of transient episodes of vertigo (1–3 s) when climbing or lifting heavy objects.” [ 35 ]. Endoscopic approaches for the surgical removal of intracochlear schwannomas with or without extension to the fundus of the IAC have also been suggested by other authors [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation